UJI SITOTOKSISITAS DAN ANTIPROLIFERATIF FRAKSI ETIL ASETAT EKSTRAK ETANOL BIJI JINTEN HITAM (Nigella sativa, Lour) TERHADAP SEL MIELOMA - Nurani, Laela Hayu (Pharmaciana, 2011)
Cancer is the formation of new tissue which is abnormal and malignant. A groupof cells suddenly become disorganized and reduplicate themselves rigorously(hyperproliferation). Nigella sativa L. is one of the herbs which have an anticancereffect. This research aims to assess the cytotoxic and antiproliferative effect of Nigellasativa L. ethanol extract of Myeloma cells. Ethanolic extract was produced fromNigella sativa L. powder with maseration method. The cytotoxicity test was done byincubating Myeloma cells with the treatment concentration group of N. sativa L. ethylacetic fraction of ethanolic extract 2000; 1000; 500; 250; and 62,5 µg/ml, respectively.The test was done with an MTT method and then with a calculation of its deathpercentage. The LC50 is calculated using a probit analysis method. The test was thencontinued with the antiproliferative test to assess the doubling time at treatmentconcentration 125; 62,5 µg/ml and cellular control at hours 24, 48, and 72. The resultsshowed that Nigella sativa L. ethanolic extract had cytotoxic activity towards theMieloma cells with an LC50 value 177,01 µg/ml. The antiproliferative test showed thatthere was a growth inhibition, even cell death at the extract treatments. The doublingtime was 253 hours at 62,5 µg/ml concentration, 298,4 hours at 125 ug/ml, while thecell control had 54,52 hours.